Polsk riksdag eller Polen gjenspeilet i norsk fraseologi - Skommer, Grzegorz (Folia Scandinavica Posnaniensia, 2007)
The article shortly outlines the uses of the lexemes Pole and Polish in Norwegian phrases and idiomatic expressions. It also provides evidence for the occurrence of the lexemes in various Danish, Norwegian and Swedish dictionaries and encyclopaedias as well as in modem Norwegian texts.